Comparison of Two Different Immobilization Devices for Pelvic Region Radiotherapy in Tomotherapy - Kim, Dae Gun; Jung, James J; Cho, Kwang Hwan; Ryu, Mi Ryeong; Moon, Seong Kwon; Bae, Sun Hyun; Ahn, Jae Ouk; Jung, Jae Hong (Progress in Medical Physics, 2016)
The purpose of this study was to compare the patient setup errors of two different immobilization devices (Feet Fix: FF and Leg Fix: LF) for pelvic region radiotherapy in Tomotherapy. Thirty six-patients previously treated with IMRT technique were selected, and divided into two groups based on applied immobilization devices (FF versus LF). We performed a retrospective clinical analysis including the mean, systematic, random variation, 3D-error, and calculated the planning target volume (PTV) margin. In addition, a rotational error (angles, o) for each patient was analyzed using the automatic image registration. The 3D-errors for the FF and the LF groups were 3.70 mm and 4.26 mm, respectively; the LF group value was 15.1% higher than in the FF group. The treatment margin in the ML, SI, and AP directions were 5.23 mm (6.08 mm), 4.64 mm (6.29 mm), 5.83 mm (8.69 mm) in the FF group (and the LF group), respectively, that the FF group was lower than in the LF group. The percentage in treatment fractions for the FF group (ant the LF group) in greater than 5 mm at ML, SI, and AP direction was 1.7% (3.6%), 3.3% (10.7%), and 5.0% (16.1%), respectively. Two different immobilization devices were affected the patient setup errors due to different fixed location in low extremity. The radiotherapy for the pelvic region by Tomotherapy should be considering variation for the rotational angles including Yaw and Pitch direction that incorrect setup error during the treatment. In addition the choice of an appropriate immobilization device is important because an unalterable rotation angle affects the setup error. KCI Citation Count: 0